Education, employment and gender gap in MENA region - Dandan, Mwafaq M. (2017)
Education is central to human capital capacity‐building, and major determinant of economic development, as it has long been considered as an important investment both for social and economic development. The Middle East and North African countries have been aware of the importance of education therefore considered it as a key part of their strategies and future planning; enrollments at different levels of education have improved dramatically over the past few decades. This study is an empirical investigation to the impact of different level of education attainment on employment level, labor force participation rate and gender gap of employment. For that purpose the cross section time series or panel data set consisting of 15 countries – where the data is comparable -has been taken. Panel data regression analysis has been carried out to find out the magnitude and direction of relationship between dependent and independent variables. Further Hausman test of specification has been applied for the selection between fixed effect model and random effect model. The main finding of this study, that there is negative relationship between educational attainment and male labor participation rate, while it is positive in case of females labor force. The study found also that with the improvement of educational attainment there has been a decrease employment gender gap.